2018
DOI: 10.1111/jep.12990
|View full text |Cite
|
Sign up to set email alerts
|

Reference centiles for the gross motor function measure and identification of therapeutic effects in children with cerebral palsy

Abstract: The presented method helps to guide the clinician to track the individual patient's gross motor development and assess the additional effect of an additionally applied intervention while taking into account the expected progression of gross motor function under standard of care.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
2

Relationship

3
3

Authors

Journals

citations
Cited by 19 publications
(45 citation statements)
references
References 22 publications
2
40
0
Order By: Relevance
“…The change related to the training was not only statistically significant, but also probably clinically relevant [ fect size for the GMFM-66 and a medium effect size for the 1MWT [18]. Further improvement in the follow-up, reflects the age-dependent natural development of the non-progressive disease, similar to findings reported among children with cerebral palsy over a six-month period [4]. Such a natural improvement is often not expected among children with progressive ataxia [21].…”
Section: Discussionsupporting
confidence: 66%
See 2 more Smart Citations
“…The change related to the training was not only statistically significant, but also probably clinically relevant [ fect size for the GMFM-66 and a medium effect size for the 1MWT [18]. Further improvement in the follow-up, reflects the age-dependent natural development of the non-progressive disease, similar to findings reported among children with cerebral palsy over a six-month period [4]. Such a natural improvement is often not expected among children with progressive ataxia [21].…”
Section: Discussionsupporting
confidence: 66%
“…Intensive training including vibration-assisted home-training, significantly improved the GMFM-66 of children with progressive and non-progressive ataxia, and the 1MWT of children with non-pro-gressive ataxia. The GMFM-66 is validated and routinely used for children with ataxic CP [4,25].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The study design has already been reported. 18 Only assessments performed using the same aids, such as splints, in all three investigations were included in the analysis.…”
Section: Study Populationmentioning
confidence: 99%
“…The methodology for the calculation of Z-scores, adjustment of skewness L(a), median value M(a) and the coefficient of variation S(a), as well as the calculation of differences between two z-scores and their correlation coefficients r, has been described in a previous publication. 18 Correlation coefficients r of the Z-Scores at M6 and M12 were used to calculate the distribution of centile changes. We further applied LOESS regression to the generated correlations coefficients r. Calculation of Z-scores was performed by applying a modified Box-Cox transformation:…”
Section: Reference Centiles and Correlationsmentioning
confidence: 99%